Effectiveness of Apigenin–Banana Stem (Musa paradisiaca) Combination Gel on Incised Wound Healing - Stiani, Sofi Nurmay; Selviani, Astri; Chairani, Farahdina; Yusransyah, Yusransyah; Udin, Baha (Sciences of Pharmacy, 2025)
Wound healing is a complex biological process involving inflammation, proliferation, and tissue remodeling. Delayed healing increases the risk of infection and other complications. Ambon banana stem (Musa acuminata) contains flavonoids, polyphenols, and tannins that support tissue regeneration, while apigenin exhibits anti-inflammatory and pro-regenerative activities. The combination of these two agents is expected to enhance wound repair. This study aimed to evaluate the effectiveness of a gel containing Ambon banana stem powder and apigenin in promoting wound healing in Sprague Dawley rats. A linear incision wound (1.5 cm × 2 mm) was created on the dorsal skin of anesthetized rats. Twenty-four male Sprague Dawley rats were divided into six groups (n = 4): untreated control (F0), negative control (gel base), positive control (Bioplacenton®), and three test formulations (F1: 5% banana stem + 10% apigenin; F2: 7.5% + 7.5%; F3: 10% + 5%). Wound length was measured daily for eight days using a digital caliper, and the percentage of wound closure was calculated. All combination gels significantly accelerated wound contraction compared with the negative control (p < 0.001). Formula F3 demonstrated the fastest healing, achieving complete closure on day 5 (1.50 ± 0.00 cm to 0.00 ± 0.00 cm), whereas the positive control reached 87.8 ± 0.15% closure by day 8. No significant differences were observed among the three test formulations. The accelerated healing is attributed to the synergistic effects of banana stem phytochemicals and apigenin. Overall, the combination gel effectively promotes wound healing and shows potential as a natural-based topical therapeutic.